1993
DOI: 10.1007/bf00190319
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary tuberculosis due to bacille Calmette-Gu�rin

Abstract: Immunotherapy using bacille Calmette-Guérin (BCG) has gained increasing acceptance in the management of superficial bladder cancer. Systemic reactions after intravesical instillation of BCG are rare. However, when the therapy is complicated, the lung often becomes involved. Since the pathogenesis of lung infiltrates after immunotherapy is unknown, we report on a patient who developed a lung infiltrate after receiving BCG immunotherapy for bladder cancer. The infectious etiology was established by culture confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…Only mild systemic symptoms, such as fever, malaise, and chills, as well as local symptoms of lower urinary tract are generally reported that usually resolve within a few hours or days. From scientific literature, we have noticed at least 37 cases of miliary pulmonary tubercolosis related to BCG instillation (4, 11-12-13-14-15-16-17-18-19-20-21-22-23-24-25-26-27-28-29-30-31-32-33-34-35-36-37-38-39-40-41-42-43-44-45-46). We know that pulmonary complications could be of two kinds: hypersensitivity and mycobacterial pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Only mild systemic symptoms, such as fever, malaise, and chills, as well as local symptoms of lower urinary tract are generally reported that usually resolve within a few hours or days. From scientific literature, we have noticed at least 37 cases of miliary pulmonary tubercolosis related to BCG instillation (4, 11-12-13-14-15-16-17-18-19-20-21-22-23-24-25-26-27-28-29-30-31-32-33-34-35-36-37-38-39-40-41-42-43-44-45-46). We know that pulmonary complications could be of two kinds: hypersensitivity and mycobacterial pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…In a series of 2,602 patients, local complications of BCG immunotherapy occurred in about 3% of patients [2]. General side effects like fever, renal abscess, sepsis and BCG-induced pulmonary [3, 4, 5]and miliary tuberculosis [6, 7]are rare and mainly reported in the form of case reports. Therefore the true incidence of systemic side effects remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Eine Literatursuche bei ¹Pubmedª ergab 12 Artikel über pulmonale Komplikationen, z. B. über Fälle mit granulomatöser Pneumonie [16] sowie Lungen-und Miliartuberkulose [9,14,18,20], die direkt durch BCG verursacht wurden oder mit hypersensiblen Reaktionen und Lungenkrankheiten assoziiert waren [1,13,15].…”
Section: Therapieunclassified